2019
DOI: 10.1186/s12974-019-1487-3
|View full text |Cite
|
Sign up to set email alerts
|

TRPV1 mediates astrocyte activation and interleukin-1β release induced by hypoxic ischemia (HI)

Abstract: Background Hypoxic-ischemic encephalopathy (HIE) is a serious birth complication with high incidence in both advanced and developing countries. Children surviving from HIE often have severe long-term sequela including cerebral palsy, epilepsy, and cognitive disabilities. The severity of HIE in infants is tightly associated with increased IL-1β expression and astrocyte activation which was regulated by transient receptor potential vanilloid 1 (TRPV1), a non-selective cation channel in the TRP famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 86 publications
2
54
0
Order By: Relevance
“…IL-1Ra, when administered in vitro, can revert this situation. Activated astrocytes can release IL-1β, which leads to tissue damage [33]. The present data showed that the expression levels of NLRP3, IL-1β and HH1R were upregulated at 1 h after OGD.…”
Section: Discussionsupporting
confidence: 49%
“…IL-1Ra, when administered in vitro, can revert this situation. Activated astrocytes can release IL-1β, which leads to tissue damage [33]. The present data showed that the expression levels of NLRP3, IL-1β and HH1R were upregulated at 1 h after OGD.…”
Section: Discussionsupporting
confidence: 49%
“…38 Janus kinase/signal transducers and activators of transcription (JAK/STAT) pathway may also be activated downstream of TRPV1 activation leading to increased expression of pro-inflammatory cytokines. 39…”
Section: Figurementioning
confidence: 99%
“…Mitochondria is a main source of reactive oxygen species (ROS) generation (Zhao et al 2019). Accumulating evidence indicates that the hypoxia and ischemic conditions result in excessive ROS generation, inflammation and apoptosis through the increase of membrane depolarization in mitochondria of neurons (Sun et al 2014;Yang et al 2019 (Caterina et al 1997). In addition to the activators, TRPV1 in neurons such as dorsal root ganglion (DRG) and hippocampus is activated by nitric oxide and ROS (Ibi et al 2008;Ogawa et al 2016).…”
Section: Introductionmentioning
confidence: 99%